Kamus Bali-Indonesia Bidang Istilah Seni Lukis Tradisional Bali - Ayu Padmasari, Ni Komang; Darsana, I Nyoman; Nala Antara, I Gde (Humanis; Vol 17 No 3 (2016), 2016)
The terminology of Balinese traditional painting in the research of Balinese-Indonesian dictionary aims to find out the form and amount of terminology in Balinese traditional painting. Theory applied are Structural linguistic developed by Ferdinand de Saussure, Lexicology and Lexicography theories. Method of collecting data applied in this research is a structural interview with the tapping technique followed by recording technique and note taking technique. In method of analyzing data, balance method is applied which a part of it is traditional method followed by basic technique, namely: selecting the determining element by subsequent technique, correlating and appealing technique and correlating and appealing main element technique. Method shared is also applied with basic technique, namely: infix technique. Method of presenting analysis data is formal and informal method by following inductive and deductive analysis technique. The result of this research is some terminologies in form of basic word contain of basic word one syllable, basic word two syllables, basic word three syllables and basic word four syllables. Derivative word contains word affixed such as prefixes, infix, suffixes, confix, and clofixes (affix joined), repeated words and compound words. The terms are phrases which are: endocentric with main one phrase consisting of: a noun phrase and numeral phrase. Terminology in form clouse is subordinative clouse. This research collects 373 terminologies.